Pandemia, adolescência e políticas sociais: processos de vulneração da vida e precarização do trabalho - Tavares, Sabrina Maria Souza (Universidade Federal de São Carlos, 2025)
The outbreak of the COVID-19 pandemic emerged within a context of structural crisis of capitalism in Brazil. Amid widespread dismantling of social policies and neglect regarding the containment and protection against the coronavirus, adolescents already living in conditions of vulnerability and rights violations became even more unprotected due to the implementation of social isolation measures, the closure of schools, and suspension of social support services. These measures intensified the risks of violence and negatively impacted their developmental processes. This dissertation derives from a nationwide, multicenter study that aimed to implement and evaluate a continuing education program for professionals in the fields of Social Assistance, Education, and Health who worked directly with socially vulnerable adolescents during and after the pandemic. The dissertation is structured in the format of two academic articles. The objective of Article 1 was to investigate, from the perspectives of professionals working in social policies, the impacts of the pandemic on the lives of vulnerable adolescents. Epistemologically grounded in Historical-Cultural Psychology, it is a mixed-methods study, with a cross-sectional and exploratory-descriptive design, derived from an intervention research project. However, only the qualitative data are presented, analyzed, and discussed in this dissertation. Data collection involved a Case Report activity and a socio-demographic and occupational characterization questionnaire. Thematic Analysis was employed for data analysis, supported by the Atlas.ti software. A total of 329 professionals from across the national territory participated in the study, the majority being women (88.4%), white (49.7%), from the Southeast region (43.5%), aged between 30 and 39 years (37%), married (39.2%), and with an individual income of one to three minimum wages (41.3%). Regarding professional characteristics, most participants worked in the field of Social Assistance (59.7%), followed by Health (23.3%) and Education (16.9%). Most had statutory employment ties (48.6%), held degrees in Social Work (38.3%), had completed a lato sensu postgraduate program (41.9%), had over ten years of professional experience (44.1%), and a 40-hour workweek (47.4%). In summary, Article 1 revealed that the pandemic worsened the living conditions of families and adolescents, with increased unemployment, food insecurity, school closures, and intensified intrafamilial violence, particularly sexual abuse, as well as child labor, psychoactive substance use, and psychological distress among adolescents. Furthermore, a decontextualized view among professionals was observed, often blaming adolescents and their families for the challenges and vulnerabilities they faced. Article 2, in turn, aimed to understand the challenges faced by professionals working in social policies in providing care and support to adolescents in situations of vulnerability during and after the pandemic. The findings indicated that professional-adolescent bonds were weakened or severed due to the closure of facilities and the replacement of in-person services with Digital Information and Communication Technologies (DICTs), leading to low adherence to proposed interventions and a fragmentation of intersectoral work. The professionals emphasized the lack of ongoing training and capacity-building to address the challenges brought on by the pandemic, highlighting the urgent need for educational initiatives that support intersectoral and transdisciplinary approaches. In this context, the pandemic represented a deepening of both the precarious living conditions of adolescents and the working conditions of professionals, who were made responsible for ensuring social protection while simultaneously experiencing losses of labor rights and the dismantling of social policies.
Pandemic, adolescence and social policies: processes of vulnerability to life and precarious work
Keywords: Pandemia; Psicologia histórico-cultural; Vulneração; Políticas sociais; Adolescence; Pandemic; Cultural-historical psychology; Vulnerability; Social policies; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO